Application of a synthetic ligand in rapidly synergistic cloud point method for separation and preconcentration trace amounts of copper of water samples. Issue 10 (8th August 2021) - Kazemi, Malihe Samadi; Jamali, Mohmmad Reza; Yazdani, Vali
Abstract: In this study, a rapidly synergistic cloud point extraction method was used to separate and pre‐concentrate small amounts of copper ions. Synthetic ligand 4‐benzylpyridine dithiocarbamate as a complexing agent, non‐ionic surfactant (Triton X‐100) as an extractant, and octanol as a synergic reagent were used. Parameters affecting copper ion extraction such as pH, ligand concentration, octanol volume, type of diluent solvent, stirring speed and time, surfactant concentration, and the effect of ionic strength were investigated. Ultraviolet‐visible spectrophotometry was used to measure the absorption of copper complex. Under optimal conditions, limit of detection, preconcentration factor, and relative standard deviation for copper were 1.4 × 10 –3 μg /mL, 10 and 2.1, respectively. Also, the relative extraction efficiency of copper extraction in real samples was greater than 97%.